2000
DOI: 10.1149/1.1393358
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Temperature Solid Oxide Fuel Cells Using LaGaO[sub 3] Electrolyte II. Improvement of Oxide Ion Conductivity and Power Density by Doping Fe for Ga Site of LaGaO[sub 3]

Abstract: Solid oxide fuel cells (SOFC) provide a new and clean electric power generating system At present, Y 2 O 3 -stabilized ZrO 2 (YSZ) is commonly used as the electrolyte of a solid oxide fuel cell. Since the oxide ion conductivity of YSZ is insufficient for the electrolyte of fuel cells, a thin electrolyte film without gas leakage and an excessively high operating temperature such as 1273 K are essential for the high power density of SOFCs when YSZ is used as electrolyte. On the other hand, all the advantages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(60 citation statements)
references
References 19 publications
1
57
0
Order By: Relevance
“…For a couple of decades, HTPCs have been recognized as particularly suitable electrolytes for IT applications, because, compared with oxygen-ion conductors, they show lower activation energy (between 0.4 and 0.6 eV) [12][13][14][15] and larger conductivity values in the IT range (figure 1) [14,[16][17][18][19]. Moreover, for HTPC-based FCs, water is produced at the cathode rather than at the anode, avoiding fuel dilution, which reduces the cell efficiency.…”
Section: Intermediate Temperature Solid Oxide Fuel Cellsmentioning
confidence: 99%
“…For a couple of decades, HTPCs have been recognized as particularly suitable electrolytes for IT applications, because, compared with oxygen-ion conductors, they show lower activation energy (between 0.4 and 0.6 eV) [12][13][14][15] and larger conductivity values in the IT range (figure 1) [14,[16][17][18][19]. Moreover, for HTPC-based FCs, water is produced at the cathode rather than at the anode, avoiding fuel dilution, which reduces the cell efficiency.…”
Section: Intermediate Temperature Solid Oxide Fuel Cellsmentioning
confidence: 99%
“…[1][2][3] Following the initial discovery, [1][2][3][4][5] numerous experimental studies have been carried out on LSGM materials, which also include the effect of transition-metal doping. [6][7][8][9][10][11] It is generally believed that doping with a transition-metal cation is undesirable for * Corresponding author. Tel.…”
Section: Introductionmentioning
confidence: 99%
“…4 Following the initial discovery, [1][2][3][4][5] numerous experimental studies have been carried out on LSGM materials, which also include the effect of transition-metal doping. [6][7][8][9][10][11] It is generally believed that doping with a transition metal cation is undesirable for the ionic conductor due to the appearance of n-or p-type conduction. However, it was found that the oxide ion conductivity was also improved by doping Co for Ga in LaGaO 3 -based perovskites, 7 although hole conduction was detected at high oxygen partial pressures.…”
Section: Introductionmentioning
confidence: 99%